Historical perspectives on infant care and development. - Norman, Amanda (London [England] : Bloomsbury, 2022)
"In understanding infant care, personal and professional, within and beyond the home, this book invites readers to explore how past events, approaches, traditions, and stories have shaped modern day practice. It introduces topics about family life, professional roles, and settings relevant to early years educators caring for infants. It contributes to the Early Education and Care (ECEC) dialogue, but with an emphasis on the Care. The chapters introduce a historical lens to topics including, pregnancy, parental relationships, the professional's role, and services available to infants. Theory and conceptual understanding from key thinkers including Rousseau, Locke, Bowlby, Vygotsky and Trevarthen are then used to contextualise the topics to contemporary practice. Each chapter includes extended reflective thinking, case studies, reflection in action and further reading to prompt additional engagement with the content."--
List of Figures -- Acknowledgements -- Introduction -- Part I: The Infant at Home -- 1. Historical Reflections and Contemporary Practice -- 2. Transitions to Parenthood -- 3. Parenting and Family Life -- 4. Infant Development and Holistic Care -- 5. The Professionalisation of Infant Care -- Part II: The Infant Beyond the Home -- 6. A Caring Community -- 7. Communication, Love and Care -- 8. Edu-care and Play -- 9. A Cross Disciplinary Approach to Studying Infants -- Conclusion: Looking Back, Moving Forward -- References -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Infants -- Care; Infants -- Development; For National Curriculum Early Years; Electronic books